2018
DOI: 10.1002/adfm.201805098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Cluster Size on Back‐Contact Perovskite Solar Cells

Abstract: Incorporating interdigitated back-contact electrodes into organic-inorganic halide perovskite solar cells overcomes the optical losses and low architectural defect tolerance present in conventional "sandwich" cell configurations. However, other factors limit device performance in back-contact architectures, such as the short charge-carrier diffusion length within the perovskite film relative to the electrode spacing. As charge-carrier diffusion length is crystal-size related, in order to understand the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…It may even be possible to efficiently transport charges over these super-grain entities, which opens up the possibility for efficient lateral or rear-contact solar cell devices 195,196 .…”
Section: [H2] Connecting the Length Scalesmentioning
confidence: 99%
“…It may even be possible to efficiently transport charges over these super-grain entities, which opens up the possibility for efficient lateral or rear-contact solar cell devices 195,196 .…”
Section: [H2] Connecting the Length Scalesmentioning
confidence: 99%
“…For the common planar type architecture, where a perovskite layer of a few hundred nm thickness is sandwiched between charge selective layers, grain sizes on that same length scale are usually sufficient to span both electrodes to ensure unhindered charge transport. When, however, the hunt for record efficiencies moves perovskite research towards back-contacted architectures as it has for conventional photovoltaics, the superior lateral conductivity of grains bridging many micrometers between electrodes may become essential for efficient charge extraction [15,41,42].…”
Section: Applicability and Perspectivesmentioning
confidence: 99%
“…[127] Such a nonsymmetric backcontacted device platform is also helpful for understanding the effect of film morphology on the optoelectrical property and the final device performance. However, the small charge-carrier diffusion length within the polycrystalline perovskite film relative to the grating electrode spacing can limit the device performance.…”
Section: Lateral Structurementioning
confidence: 99%
“…However, the small charge‐carrier diffusion length within the polycrystalline perovskite film relative to the grating electrode spacing can limit the device performance. By changing the perovskite films grain sizes in the bc‐PSC, Bach and co‐workers further found that the charge‐carrier diffusion length is crystal‐size dependent and the device performance correlates positively with the perovskite grain size . Such a nonsymmetric back‐contacted device platform is also helpful for understanding the effect of film morphology on the optoelectrical property and the final device performance.…”
Section: Etl‐free Pscs In Varying Structuresmentioning
confidence: 99%